THE TRACES OF ISLAMIC CULTURAL HISTORY: ANALYZING THE CULTURAL VALUES THAT INSPIRE INDONESIAN MUSLIMS - Abdul Wahab Syakhrani; Agus Fawait; Zainol Hasan; Antono Damayanto; Heru Widoyo (Adisam Publisher, 2026)
The article